1999
DOI: 10.1097/00003246-199910000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation in the hospital: Differential relationships between age and survival across rhythms

Abstract: The relationship between patient age and a successful resuscitation attempt is not as simple as reported earlier. Whether age is related to increased or decreased survival, or is unrelated to survival, depends on the rhythm extant when resuscitation attempts begin. Survival rates were higher than most reported elsewhere and improved significantly over time. Multicentered studies are needed to determine whether these results are unique to the institution studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Previous clinical reports have focused largely on the SCA event, attributing manifestation of PEA to a variety of factors including hypoxia, hypovolemia, electrolyte imbalance, tamponade, pneumothorax, and thromboembolism. 27 Consistent with several earlier reports in the literature, 18,28,29 we observed that pulmonary disease was associated with increased frequency of PEA.…”
Section: Discussionsupporting
confidence: 91%
“…Previous clinical reports have focused largely on the SCA event, attributing manifestation of PEA to a variety of factors including hypoxia, hypovolemia, electrolyte imbalance, tamponade, pneumothorax, and thromboembolism. 27 Consistent with several earlier reports in the literature, 18,28,29 we observed that pulmonary disease was associated with increased frequency of PEA.…”
Section: Discussionsupporting
confidence: 91%
“…Neurological outcomes were comparable between groups. The better survival in patients presenting in VT/VF has been reported for in-hospital arrests by a number of other investigators (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 60%
“…Similar observation can be found in the literature. Age, used as a continuous variable, was strongly related to survival (odds ratio = 0.984; P < 0.0001) in a study by Parish et al 17,18 Presence of comorbidities prevented successful outcome after CPR. A survival rate of 64% has been shown in out audit in patients with no co-morbidities.…”
Section: Discussionmentioning
confidence: 97%